REWARDS, WORK STRESS, PUNISHMENT AND THEIR IMPACT ON EMPLOYEE PERFORMANCE CV. SARAO ESA PRIMA - HW, Sabetheo; Febriana, Artha (Universitas Dian Nuswantoro, 2024)
This research aims to analyze and find out how rewards, work stress and punishment influence employee performance at CV. Sarao Esa Prima. The objects of this research are all CV employees. Sarao Esa Prima. as many as 51 employees. In determining the sample size, researchers used the census method where all members of the population were used as the research sample. The number of samples in this research was 51 employees. Trials of research items were carried out on 15 employees. Validity test uses Pearson Product Moment correlation. Meanwhile, the reliability test uses Cronbach Alpha. Data collection techniques include questionnaires, observation and documentation. Analysis prerequisite tests include normality tests, multicollinearity tests and heteroscedasticity tests. The data analysis technique used is multiple linear regression. The research results show that: (1) Rewards have a positive and significant effect on employee performance. (2) Job stress has a negative and significant effect on employee performance. (3) Punishment has no significant effect on employee performanc